Paste-containing silty sandy mudstone modification method and modifier component content determination method
By using cement, polypropylene fiber and sodium methyl silicate as modified agents in paste-containing silt mudstone, the problems of low strength and poor water stability in engineering applications are solved, and higher compressive strength and permeability are achieved, which extends the service life of the roadbed and promotes the resource utilization of solid waste.
Patent Information
- Application Number
- CN202510017793.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-06
AI Technical Summary
Paste-containing silt sandy mudstones have problems of low strength, poor water stability and strong corrosiveness in engineering applications, resulting in environmental damage and challenges in transportation infrastructure.
Cement, polypropylene fiber and sodium methyl silicate are used as modification agents to improve the strength and stability of the paste-containing silt mudstone.
It significantly improves the compressive strength, crack resistance and permeability of the modified soil, extends the service life of the roadbed, reduces the dependence on high-quality fillers, and realizes the resource utilization of bulk solid waste.
Smart Images

Figure CN119822727A_ABST
Abstract
Description
Technical Field
[0001] The present specification relates to the field of modification of silty sandy mudstone containing grease, and more specifically, the present application relates to a method for modifying silty sandy mudstone containing grease and a method for determining the content of modifier components. Background Art
[0002] In some areas, a special chemical sedimentary rock, namely, gypsum-containing sandy mudstone, is widely distributed. Transportation projects inevitably pass through gypsum-containing sandy mudstone. However, gypsum-containing sandy mudstone, which has low strength, poor water stability and strong corrosiveness, brings challenges and risks to the environment and transportation infrastructure. Specifically, (1) The excavation and waste of gypsum-containing sandy mudstone tunnels seriously damage the ecological environment. (2) The roadbed of gypsum-containing sandy mudstone is severely deformed, and it is generally difficult to obtain high-quality filling materials in western Sichuan. How to achieve the goal of improving the waste of gypsum-containing sandy mudstone tunnels for roadbed filling, and then achieve the goals of carbon peak and carbon neutrality, sustainable resource development and reducing the impact on the ecological environment, is one of the major problems that the engineering community urgently needs to solve.
[0003] Therefore, it is necessary to propose a method for modifying gypsum-containing sandy mudstone and a method for determining the content of modifier components. Summary of the invention
[0004] A series of simplified concepts are introduced in the Summary of the Invention section, which will be further described in detail in the Detailed Description of the Invention section. The Summary of the Invention section of this application does not mean to attempt to define the key features and essential technical features of the claimed technical solution, nor does it mean to attempt to determine the scope of protection of the claimed technical solution.
[0005] In the first aspect, the present application proposes a method for modifying gypsum-containing sandy mudstone, the method comprising: Making an improver based on cement, polypropylene fibers and sodium methyl silicate; The above-mentioned improver is used to mix and modify the above-mentioned paste-containing sandy mudstone to obtain modified rock and soil.
[0006] In a feasible implementation manner, the total mass of the above-mentioned improver is calculated as a percentage, and the above-mentioned improver includes: 2% to 6% of the above-mentioned cement, 0.25% of the above-mentioned polypropylene fiber, and 0.25% to 0.5% of the above-mentioned sodium methyl silicate.
[0007] In a feasible embodiment, the cement includes sulfate-resistant silicate cement, the length of the polypropylene fiber is 6 mm, the diameter of the polypropylene fiber is 23 um, the solid content of the sodium methyl silicate is 30%, the alkali content of the sodium methyl silicate is less than or equal to 12%, the silicone content of the sodium methyl silicate is greater than or equal to 18%, the specific gravity of the sodium methyl silicate is greater than or equal to 1.2 and less than or equal to 1.25, and the pH value of the sodium methyl silicate is greater than or equal to 12 and less than or equal to 13.
[0008] In a second aspect, the present application provides a method for determining the content of a modifier component, which is used for the modifier described in any one of the first aspects, comprising: Determine the basic components of the above-mentioned improver based on the water dispersibility experiment, and the above-mentioned basic components include the above-mentioned cement, the above-mentioned polypropylene fiber and the above-mentioned sodium methyl silicate; An orthogonal test is conducted based on soil samples modified with the above-mentioned improvers to obtain preliminary component information of the improvers; The soil samples modified by the above-mentioned modifiers are subjected to XRD test, expansion test and expansion force test to further narrow the preliminary component information of the above-mentioned modifiers to obtain the narrowed component information; The target ratio of the improver was determined based on the 7D saturated compressive strength test and the micro-electron microscopy scanning test.
[0009] In a feasible implementation, the orthogonal experiment includes a liquid-plastic limit combined determination test, a compaction test and a shear strength test, and the expansion test includes a free expansion test, a no-load expansion rate test and a loaded expansion rate test.
[0010] In a feasible implementation, the orthogonal test is performed on the soil sample modified by the above-mentioned modifier to obtain the preliminary component information of the modifier, including: Determine the primary content of cement in the above-mentioned improver based on the above-mentioned liquid limit and plastic limit combined determination test; The primary content of polypropylene fiber and the primary content of sodium methyl silicate in the above-mentioned improver are determined based on the above-mentioned compaction test and the above-mentioned shear strength test.
[0011] In a feasible implementation, the soil sample modified by the above-mentioned modifier is subjected to XRD test, expansion test and expansion force test to further limit the preliminary component information of the above-mentioned modifier to obtain the limited component information, including: Based on the soil samples modified by the above-mentioned modifiers, XRD tests, swelling tests and swelling force tests are carried out to extract corresponding characteristic indicators and weight information corresponding to the characteristic indicators; Determine the mechanical property evaluation index based on all the above characteristic indicators and the weight information corresponding to the above characteristic indicators; Based on the above mechanical property evaluation index, the preliminary component information of the above improver is further restricted to obtain the above restricted component information.
[0012] In a feasible implementation manner, the mechanical property evaluation index is determined based on all the above characteristic indicators and the weight information corresponding to the above characteristic indicators, including: The performance evaluation index is calculated based on the following formula : in, is the number of all participating trials, For the The weight of the test results, For the The characteristic index value of each test, RD test characteristic indicators It is the mineral content ratio and characteristic index of free expansion test It is the free expansion rate and characteristic index of no-load expansion rate test It is the characteristic index of no-load expansion rate and loaded expansion rate test It is the load expansion rate and expansion force test characteristic index for expansion force; Based on the above mechanical property evaluation index, the preliminary component information of the above improver is further limited to obtain the above limited component information, including: A formula regression model is established based on historical test data, wherein the above formula regression model is based on the above mechanical properties evaluation , cement target content, polypropylene fiber target content and sodium methyl silicate target content; Determine the shrinkage limiting component information according to the mechanical property evaluation index and the formula regression model, wherein the shrinkage limiting component information includes a target cement content, a target polypropylene fiber content, and a target sodium methyl silicate content in the improver; The above formulation regression model is determined based on the following formula: in, is the target cement content, is the target content of polypropylene fiber, is the target content of sodium methyl silicate, and a, b, c, d, f, g and h are parameters obtained by regression fitting.
[0013] In a feasible implementation, it also includes: Modifying the roadbed material based on the modifier corresponding to the content of the modifier component to obtain a modified roadbed material; A dynamic triaxial test is performed based on the modified roadbed material to obtain a first test result; Conducting a simulation test based on the modified roadbed material to obtain a second test result; The content of the above-mentioned improver component is optimized based on the above-mentioned first test results and the above-mentioned second test results.
[0014] In a feasible implementation manner, the above-mentioned simulation test is implemented based on a scale model established based on COMSOL software, and the above-mentioned scale model includes rails, CA mortar layers, track plates, roadbeds and foundation structures. The above-mentioned scale model is a two-dimensional model, and the load in the above-mentioned simulation test is a half-sine wave pulse. In the above-mentioned simulation test, infinite domain boundaries are used on the foundation and cross-section.
[0015] In summary, this method uses cement as the main modifier to generate cementing products such as calcium silicate hydrate (CSH) through hydration reaction, which effectively improves the initial strength and overall bearing capacity of the soil. 2+ and SO4 2-The reaction generates stable compounds, which reduces the negative impact of the paste on the strength of the soil. The modified paste-containing silty mudstone has higher compressive strength and bearing capacity, and can be widely used in road and railway engineering. The paste-containing silty mudstone is prone to shrinkage cracks under the action of dry-wet cycles, affecting the long-term stability of the roadbed. Polypropylene fibers are introduced into the modifier in this method to form a "fiber network", which significantly enhances the crack resistance and tensile strength of the soil. Polypropylene fibers effectively limit the expansion of cracks, improve the toughness and deformation resistance of the modified soil, and extend the service life of the roadbed. The paste-containing silty mudstone has significant water absorption and expansion and water loss shrinkage, resulting in serious engineering deformation and poor water stability. The modifier in this method has strong anti-permeability properties after the addition of sodium methyl silicate, which can reduce the entry of water into the soil, thereby reducing its water absorption and expansion. Sodium methyl silicate reacts with active minerals in the soil to form a water-insoluble silicate film, which further improves the stability and hydrolysis resistance of the soil. The impermeability and anti-expansion properties of the soil are significantly enhanced, and it can be effectively applied in areas with complex water environments (such as western Sichuan). The large amount of spoil generated by the excavation of the tunnel containing gypsum powder sandy mudstone causes serious damage to the environment, and it is difficult to obtain high-quality roadbed fillers, resulting in serious waste of resources. By modifying the spoil containing gypsum powder sandy mudstone, it is converted into high-performance roadbed fillers, reducing the dependence on high-quality fillers. The resource utilization of bulk solid waste is achieved, the amount of tunnel spoil is reduced, and the damage to the ecological environment is reduced. Traditional modification research is mainly based on single-addition or double-addition improved materials, and a systematic study of multi-addition and multi-proportion modification has not been formed. This method proposes a modification method based on multiple additions and multiple proportions (cement, polypropylene fiber, sodium methyl silicate). The traditional method has poor adaptability on the construction site and often requires complex equipment or strict conditions. This method adopts standardized mixing ratios and simple mechanical mixing methods, which can be directly applied on the construction site, is easy to operate, has a short mixing time, and ensures construction efficiency. The amount of water added can be adjusted according to the natural moisture content of the soil to meet the needs of different regions and environments. Traditional methods are difficult to ensure the long-term durability of the soil, especially in acidic and sulfate-corroded environments. The use of sulfate-resistant cement significantly enhances the sulfate-corrosion resistance of the modified soil and prolongs its service life. The hydrophobicity and chemical stability of sodium methyl silicate enable the modified soil to maintain good performance in complex environments. The traditional method has a high modification cost and is destructive to the environment. The dosage design of the modifier is scientific and reasonable, and the amount used is small (such as cement is only 2% to 6%, polypropylene fiber is 0.25%, and sodium methyl silicate is 0.25% to 0.5%), which reduces the material cost. It reduces the exploitation of natural resources (such as high-quality fillers) and reduces the damage to the ecological environment, which has significant environmental benefits.This method effectively overcomes the problems of low strength, poor water stability and strong corrosiveness of paste-containing sandy mudstone in the background technology by scientifically designing the improver components and blending process, significantly improves the strength, stability and durability of the modified soil, realizes resource utilization and green development, and has significant engineering value and social benefits.
[0016] The method proposed in the present application, and other advantages, objectives and features of the present application will be reflected in part through the following description, and in part will be understood by those skilled in the art through research and practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present specification. Also, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings: Figure 1 A schematic diagram of the process of modifying a paste-containing sandy mudstone provided in an embodiment of the present application; Figure 2 This is an electron microscope image of the surface morphology of anhydrite before modification of a gypsum-containing silty mudstone provided in an embodiment of the present application; Figure 3 This is a 50x electron microscope image of the surface morphology of anhydrite modified from a paste-containing silty mudstone provided in an embodiment of the present application; Figure 4 This is an electron microscope image of the toughness and strength changes of a gypsum-containing sandy mudstone before modification provided in an embodiment of the present application; Figure 5 This is a 25x electron microscope image of the toughness and strength change of a modified silty mudstone containing paste provided in an embodiment of the present application; Figure 6 This is a 100x electron microscope image of the toughness and strength change of a modified gypsum-containing sandy mudstone provided in an embodiment of the present application; Figure 7 This is a 500x electron microscope image of the toughness and strength change of a modified silty mudstone containing paste provided in an embodiment of the present application; Figure 8 This is a 50x electron microscope image of the surface voids and pore changes of a paste-containing silty mudstone after C0 modification provided in the examples of the present application; Fig. 9 This is a 50x electron microscope image of the surface voids and pore changes of a paste-containing silty mudstone after being modified by XCF1 provided in the examples of the present application; Fig.10 This is a 50x electron microscope image of the surface voids and pore changes of a paste-containing silty mudstone after being modified by XCF2 provided in the examples of the present application; Fig.11 This is a 50x electron microscope image of the surface voids and pore changes of a paste-containing silty mudstone after being modified by XCF3 provided in the examples of the present application; Fig.12 This is a 100x electron microscope image of the surface voids and pore changes of a gypsum-containing silty mudstone after C0 modification provided in an embodiment of the present application; Fig.13 This is a 100x electron microscope image of the surface voids and pore changes of a paste-containing silty mudstone after being modified by XCF1 provided in the examples of the present application; Fig.14 This is a 100x electron microscope image of the surface voids and pore changes of a paste-containing silty mudstone after being modified by XCF2 provided in the examples of the present application; Fig.15 This is a 100x electron microscope image of the surface voids and pore changes of a paste-containing silty mudstone after being modified by XCF3 provided in the examples of the present application; Fig.16 A schematic diagram of a method for determining the content of a modifier component provided in an embodiment of the present application Fig.17 A simulation model original model diagram provided in an embodiment of the present application; Fig.18 A partial enlarged view of mesh division of a simulation model provided in an embodiment of the present application; Fig.19 This is a 2Hz numerical simulation diagram of various parts before and after improvement provided in an embodiment of the present application. DETAILED DESCRIPTION
[0018] The terms "first", "second", "third", "fourth", etc. (if any) in the specification and claims of this application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments described herein can be implemented in a sequence other than that shown or described. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0019] As one of the major types of solid waste in the transportation sector, waste rock, namely gypsum-containing silty mudstone, appears on a large scale in road and railway projects. In the past, it was generally solved as an adverse geological problem. Gypsum-containing rocks, as a sedimentary rock of evaporation origin, are widely distributed throughout my country, especially in sea basins or lake basins. They have developed in almost every geological era, especially in North China and Southwest my country. Therefore, due to the special formation environment, it has special engineering geological characteristics. The main content of gypsum is Ca 2+ and SO4 2- and two water molecules. Under the influence of the outside world, the two water molecules are prone to shrinkage due to water loss and expansion due to water absorption, and Ca 2+ and SO4 2- It will also cause damage to buildings, thus causing harm to actual projects. At present, most of the improved soils are mainly silty mudstone, mudstone, etc., and the research on improved materials is mainly single-mixed or double-mixed. There are few studies on the use of multiple dosages and multiple proportions of improvers to improve paste-containing silty mudstone and use physical and mechanical tests, microscopic analysis, and road deformation characteristics.
[0020] See also Figure 1 , which is a schematic diagram of the process of modifying a paste-containing silty mudstone provided in an embodiment of the present application, and may specifically include: S110, improver based on cement, polypropylene fiber and sodium methyl silicate; Exemplarily, the improver is composed of three main components: cement, polypropylene fiber and sodium methyl silicate. The function and role of each component are as follows: Cement provides initial strength and generates hydration products (such as Ca(OH)2) through hydration reaction, which fills the pores in the soil and enhances the overall strength of the soil. 2+ and SO4 2- Interact with each other to reduce the negative impact of paste on soil stability. Cement plays a bonding and filling role in improved soil and is the core material for improving bearing capacity.
[0021] Polypropylene fiber enhances the crack resistance and tensile strength of soil, improves the toughness of modified soil, provides soil with a certain degree of deformation resistance, and reduces the occurrence of shrinkage cracks. Polypropylene fiber is a polymer material with excellent tensile strength and durability, and is particularly suitable for soil reinforcement.
[0022] Sodium methyl silicate improves the impermeability and durability of the soil, reduces water infiltration, and thus reduces the water absorption and expansion of the paste. It reacts with the mineral components in the soil to form water-insoluble silicates, further improving the stability of the soil. Sodium methyl silicate is an organic silicon modifier that has both chemical and physical modification effects.
[0023] S120. The above-mentioned paste-containing sandy mudstone is mixed and modified by using the above-mentioned modifier to obtain modified rock and soil.
[0024] For example, remove impurities in the soil, such as large stones, tree roots, etc. Crush the waste to the designed particle size (usually in the range of 0.075mm to 2mm) as needed to ensure uniform particle size distribution. Test the basic performance parameters of the soil (such as natural moisture content, particle size distribution, Ca 2+ and SO4 2- content, etc.), to provide a reference for subsequent blending and modification.
[0025] According to the specific characteristics of the soil, combined with the regression formula and the target performance, determine the addition ratio of the modifier. Add the modifier to the soil in the order of cement, polypropylene fiber and sodium methyl silicate to ensure the uniform distribution of each material. Use a mixer (such as a drum mixer or a rotary mixer) to fully mix the modifier with the soil to ensure the uniform distribution of the materials. Manual mixing can be used for small-scale tests, but the mixing time and strength need to be strictly controlled. Usually the mixing time can be 5 to 15 minutes to ensure that the modifier is fully in contact and dispersed with the soil particles. According to the natural moisture content of the soil, calculate the amount of water to be added to achieve the target moisture content of the modified soil, for example, 8% to 15%. After adding water, continue stirring to ensure that the cement hydration reaction and the chemical reaction of sodium methyl silicate are fully carried out. This process will produce cementing products such as hydrated calcium silicate and silicates, which significantly improve the mechanical properties and stability of the soil.
[0026] In summary, this method uses cement as the main modifier to generate cementing products such as calcium silicate hydrate (CSH) through hydration reaction, which effectively improves the initial strength and overall bearing capacity of the soil. 2+ and SO4 2-The reaction generates stable compounds, which reduces the negative impact of the paste on the strength of the soil. The modified paste-containing silty mudstone has higher compressive strength and bearing capacity, and can be widely used in road and railway engineering. The paste-containing silty mudstone is prone to shrinkage cracks under the action of dry-wet cycles, affecting the long-term stability of the roadbed. Polypropylene fibers are introduced into the modifier in this method to form a "fiber network", which significantly enhances the crack resistance and tensile strength of the soil. Polypropylene fibers effectively limit the expansion of cracks, improve the toughness and deformation resistance of the modified soil, and extend the service life of the roadbed. The paste-containing silty mudstone has significant water absorption and expansion and water loss shrinkage, resulting in serious engineering deformation and poor water stability. The modifier in this method has strong anti-permeability properties after the addition of sodium methyl silicate, which can reduce the entry of water into the soil, thereby reducing its water absorption and expansion. Sodium methyl silicate reacts with active minerals in the soil to form a water-insoluble silicate film, which further improves the stability and hydrolysis resistance of the soil. The impermeability and anti-expansion properties of the soil are significantly enhanced, and it can be effectively applied in areas with complex water environments (such as western Sichuan). The large amount of spoil generated by the excavation of the tunnel containing gypsum powder sandy mudstone causes serious damage to the environment, and it is difficult to obtain high-quality roadbed fillers, resulting in serious waste of resources. By modifying the spoil containing gypsum powder sandy mudstone, it is converted into high-performance roadbed fillers, reducing the dependence on high-quality fillers. The resource utilization of bulk solid waste is achieved, the amount of tunnel spoil is reduced, and the damage to the ecological environment is reduced. Traditional modification research is mainly based on single-addition or double-addition improved materials, and a systematic study of multi-addition and multi-proportion modification has not been formed. This method proposes a modification method based on multiple additions and multiple proportions (cement, polypropylene fiber, sodium methyl silicate). The traditional method has poor adaptability on the construction site and often requires complex equipment or strict conditions. This method adopts standardized mixing ratios and simple mechanical mixing methods, which can be directly applied on the construction site, is easy to operate, has a short mixing time, and ensures construction efficiency. The amount of water added can be adjusted according to the natural moisture content of the soil to meet the needs of different regions and environments. Traditional methods are difficult to ensure the long-term durability of the soil, especially in acidic and sulfate-corroded environments. The use of sulfate-resistant cement significantly enhances the sulfate-corrosion resistance of the modified soil and prolongs its service life. The hydrophobicity and chemical stability of sodium methyl silicate enable the modified soil to maintain good performance in complex environments. The traditional method has a high modification cost and is destructive to the environment. The dosage design of the modifier is scientific and reasonable, and the amount used is small (such as cement is only 2% to 6%, polypropylene fiber is 0.25%, and sodium methyl silicate is 0.25% to 0.5%), which reduces the material cost. It reduces the exploitation of natural resources (such as high-quality fillers) and reduces the damage to the ecological environment, which has significant environmental benefits.This method effectively overcomes the problems of low strength, poor water stability and strong corrosiveness of paste-containing sandy mudstone in the background technology by scientifically designing the improver components and blending process, significantly improves the strength, stability and durability of the modified soil, realizes resource utilization and green development, and has significant engineering value and social benefits.
[0027] In some examples, the total weight of the above-mentioned improver is calculated as a percentage, and the above-mentioned improver includes: 2% to 6% of the above-mentioned cement, 0.25% of the above-mentioned polypropylene fiber, and 0.25% to 0.5% of the above-mentioned sodium methyl silicate.
[0028] In some examples, the cement includes sulfate-resistant silicate cement, the length of the polypropylene fiber is 6 mm, the diameter of the polypropylene fiber is 23 um, the solid content of the sodium methyl silicate is 30%, the alkali content of the sodium methyl silicate is less than or equal to 12%, the silicone content of the sodium methyl silicate is greater than or equal to 18%, the specific gravity of the sodium methyl silicate is greater than or equal to 1.2 and less than or equal to 1.25, and the pH value of the sodium methyl silicate is greater than or equal to 12 and less than or equal to 13.
[0029] For example, in the composition and proportion of the modifier, the total mass percentage of cement can be 2% to 6%, and the cement type can be sulfate-resistant silicate cement. Sulfate-resistant cement has a strong ability to resist sulfate erosion and can effectively deal with SO4 in the clay-containing soil. 2- When cement is mixed with water, it produces cementing products such as calcium silicate hydrate (CSH gel), which improves the strength and stability of the soil.
[0030] The total mass percentage of the polypropylene fiber can be 0.25%. The length can be 6 mm and the diameter can be 23 μm. The length of 6 mm and the diameter of 23 μm ensure that the fiber is evenly distributed in the soil and can form an effective "reinforcement" effect. The polypropylene fiber can improve the crack resistance, tensile strength and toughness of the soil, and prevent cracks from occurring during shrinkage or swelling of the soil.
[0031] The total mass percentage of sodium methyl silicate is 0.25% to 0.5%, the solid content is 30%, the alkali content is ≤12%, the silicone content: ≥18%, 1.2≤ specific gravity ≤1.25. 12≤ pH value ≤ 13. High silicone content can improve the reaction ability with active minerals (such as silica) in the soil, forming water-insoluble silicate compounds, and significantly improving the impermeability of the soil. Alkali content control can ensure that it has no adverse chemical effects on other components (such as fiber, cement) during the soil modification process. High pH value provides a strong alkaline environment, promotes silication reaction, and improves the soil's resistance to expansion and hydrolysis.
[0032] Low cement content (2% to 6%), through the superior performance of sulfate-resistant silicate cement, can reduce the amount of cement while still ensuring the strength and durability of the modified soil and reducing material costs. Low polypropylene fiber content (0.25%), although the amount of polypropylene fiber is small, its high-efficiency reinforcement effect makes the soil have good crack resistance.
[0033] Low sodium methyl silicate dosage (0.25%~0.5%) Due to its high activity, a small amount of sodium methyl silicate can significantly improve the impermeability and stability of the soil and avoid material waste.
[0034] The synergistic effect of cement, fiber and sodium methyl silicate: cement provides basic strength, propylene fiber improves the crack resistance and toughness of the soil, and sodium methyl silicate improves impermeability and chemical stability. The synergistic effect of the three ensures that the modified soil is comprehensively improved in terms of mechanical properties and durability.
[0035] This method significantly improves the engineering applicability of gypsum-containing sandy mudstone through scientific material selection (anti-sulfate cement, high-performance polypropylene fiber, sodium methyl silicate) and precise dosage design. The modified soil has high strength, good crack resistance, excellent durability and impermeability, which can meet the needs of road and railway projects and provide a reliable solution for the resource utilization of bulk solid waste.
[0036] As shown in Table 1, the ratios of several improvers are as follows: Table 1 Improver ratio table Improver Type Ratio No. Dosage design Cement content (%) Cement: Polypropylene fiber (mass ratio) Sodium methyl silicate(%) cement C-0 Single doping 2 - - Cement + polypropylene fiber XCF1 Three-doping 2 8:1 2 Cement + polypropylene fiber XCF2 Three doping 4 8:1 2 Cement + polypropylene fiber XCF3 Three-doping 6 8:1 2 like Figures 2 to 10 As shown, Figure 2 It can be seen that the gypsum before improvement is in the form of crystals, directly exposed on the surface, and the gypsum after improvement is in the form of crystals. Figure 3 As shown in the figure, its surface is covered with a layer of covering. This is because under the action of sodium methyl silicate, it reacts with water molecules to form a tightly bound, non-permeable methyl silicate waterproof film attached to the surface of the gypsum crystal, preventing water molecules from penetrating into the gypsum crystal, thereby effectively inhibiting the absorption of water by anhydrite and the occurrence of adverse geological phenomena such as expansion and dissolution caused by the scouring of running water.
[0037] from Figures 4 to 7 It can be seen from the figure that after adding polypropylene fibers, the fibers in the soil can be found to cross and shuttle from all directions of the sample to form a network constraint. Therefore, this structure can not only improve the toughness of the soil, but also provide an attachment place for the polymer formed after the cement and sodium methyl silicate react with the substances in the soil. The fibers can form a bonding coupling relationship with the polymer, further enhancing the cohesion and constraint between the formed grids.
[0038] Figures 8 to 11From the analysis, we can know that the soil sample is loose on the macroscopic surface, with large gaps and obvious cracks between the soil particles, and no obvious cementing material between the particle surface and the gaps. Therefore, the strength of the soil is low and the bearing capacity is poor in this state. In the process of rainfall, water can easily penetrate into the soil, causing the strength of the soil to further decrease. Therefore, the original soil is not suitable for direct filling as roadbed soil. From the 1000x scanning electron microscope, it can be seen that with the addition of cement, from the perspective of surface morphology and structure, compared with the loose stacking state in the initial state, the improved Fig.13 The soil particles are in the form of small lumps, and gradually develop into block, column, and lump forms as the cement content increases. Fig.14 and Fig.15 , and polymers are formed on the surface of soil particles, which are connected to each other in a network structure. These forms can greatly enhance the structural strength of the soil. From the perspective of voids and pores, with the addition of modifiers, the number of voids is significantly reduced, and it is nonlinearly inversely proportional to the increase in cement content. The generated polymers obviously fill the voids, and the pore range is gradually reduced from the original network-like structure, and finally becomes local short and narrow small pores.
[0039] Therefore, from the microscopic level, it can be analyzed that the improved soil not only reduces the number of voids, reduces the degree of pore development, and changes the connection between soil particles, but also enhances the toughness through the incorporation of polypropylene fibers, forming a bonding coupling relationship with the polymer, and the waterproofing agent generated by the reaction of sodium methyl silicate and water protects the expansion of anhydrite and the dissolution of gypsum, thereby improving the engineering mechanical properties of the entire soil.
[0040] Second, Fig.16 As shown, the present application proposes a method for determining the content of a modifier component, which is used to determine the modifier described in any one of the first aspects, comprising: S210, determining the basic components of the above-mentioned improver based on a water dispersibility experiment, wherein the above-mentioned basic components include the above-mentioned cement, the above-mentioned polypropylene fiber and the above-mentioned sodium methyl silicate; For example, according to previous studies, the gypsum sandy mudstone in the study area has low liquid limit, low strength, poor grading and poor hydraulic properties. Therefore, based on the experience of soil improvement and the characteristics of gypsum sandy mudstone in the study area, inorganic and organic modifiers were selected for comprehensive improvement. The inorganic modifiers were fly ash, cement and lime; the organic modifiers were polypropylene fiber and sodium methyl silicate. The specimen size was 50mm×50mm, and it was cured for 24 hours under standard conditions. The improvement plan was finally determined through this short-term water stability test. The ratio of the primary modifier and the state after saturation are shown in Table 2.
[0041] Table 2 The ratio of the primary improver and the corresponding state after saturation Improver Inorganic modifier dosage (%) 1D 7D 14D cement 6 Undispersed Undispersed Undispersed lime 6 Undispersed Scatter Undispersed Fly ash 6 Undispersed Scatter Undispersed Cement: Polypropylene fiber = 12:1 6 Undispersed Undispersed Undispersed Lime: Polypropylene fiber = 12:1 6 Undispersed Scatter Scatter Fly ash: polypropylene fiber = 12:1 6 Undispersed Scatter Scatter Cement: polypropylene fiber: sodium methyl silicate = 12:1:4 6 Undispersed Undispersed Undispersed Lime: polypropylene fiber: sodium methyl silicate = 12:1:4 6 Undispersed Scatter Scatter Fly ash: polypropylene fiber: sodium methyl silicate = 12:1:4 6 Undispersed Scatter Scatter As shown in Table 2, after the water dispersibility test, it was found that only the sample improved with cement could remain intact after 14 days, while the others had become loose. Based on the experience of improving poor soil, the results of general roadbed soil filling improvement tests and the special circumstances of this test, after preliminary screening, it was decided to use cement + polypropylene fiber + sodium methyl silicate as the main improver combination.
[0042] The basic parameters of sulfate-resistant cement can be determined according to Table 3: Table 3 Basic parameters of sulfate-resistant cement Element <![CDATA[SiO2]]> CaO <![CDATA[Fe2O3]]> <![CDATA[Al2O3]]> MgO <![CDATA[Na2O]]> <![CDATA[SO3]]> content(%) 22.77 53.25 5.16 8.27 1.84 0.37 2.34 The basic parameters of polypropylene fiber can be determined according to Table 4: Table 4 Basic parameters of polypropylene fiber Acid and alkali resistance Length (mm) Diameter (μm) Elastic modulus (MPa) Breaking strength (MPa) Elongation at break Security Density (g / cm³) powerful 6 23 3800 600 13 Non-toxic 1.38 S220, conducting an orthogonal test on the soil sample modified by the above-mentioned modifier to obtain preliminary component information of the modifier; For example, the orthogonal test design method is used to systematically analyze the effects of different modifier components on the properties of modified soil, so as to determine the initial range of modifier component proportions. According to the test variables (such as the dosage of cement, polypropylene fiber, and sodium methyl silicate) and the response indicators (such as strength and expansibility), an orthogonal test table is designed. For example, three factors (cement dosage, fiber dosage, sodium methyl silicate dosage) are selected, and each factor is set at different levels (such as high, medium, and low) to form an orthogonal test table, and the physical and mechanical properties of the test samples are tested (such as compressive strength and expansibility). Analyze the results of the orthogonal test, determine the degree of influence of each factor on the target performance, and screen out the initial modifier components and their approximate proportion range.
[0043] S230, performing an XRD test, a swelling test and a swelling force test on the soil sample modified by the above-mentioned modifier to further limit the preliminary component information of the above-mentioned modifier to obtain limited component information; For example, further chemical and physical tests are performed to verify the effectiveness of the preliminarily selected components and to narrow the range of components to ensure that the performance of the modified soil sample is optimized.
[0044] XRD test (X-Ray Diffraction) is used to analyze the changes in mineral components in modified soil, especially the formation of cement hydration products and sulfate minerals. The test is used for judgment and screening, and the XRD phase analysis method is used to determine the improvement effect by measuring the relative content of CaSO4 and CaSO4·2H2O in the improved material.
[0045] The swelling test is used to measure the volume change of modified soil samples under water absorption to evaluate the inhibitory effect of the modifier on swelling. The soil sample is saturated with water, and the swelling rate is recorded and compared with the unmodified soil sample.
[0046] The expansion force test is used to determine the vertical expansion force generated by soil on the constrained environment during the process of water absorption and expansion. The modified soil sample is placed in the expansion force tester to record the stress changes during the expansion of the soil sample.
[0047] According to the results of XRD test, expansion test and expansion force test, the components and proportions of the shrinkage modifier are screened and limited to ensure that it can effectively improve the expansion, strength and other properties.
[0048] S240, determine the target ratio of the improver based on the 7D saturated compressive strength test and micro-electron microscope scanning test.
[0049] Exemplarily, the performance of the improver is verified through further mechanical property testing and microscopic analysis, and its target ratio is finally determined.
[0050] The 7D saturated compressive strength test is used to evaluate the compressive strength of modified soil in a 7-day saturated state, reflecting the water stability and bearing capacity of the soil. Modified soil samples with different proportions are prepared and cured in a saturated environment for 7 days. The compressive strength values of the samples are measured using a compressive strength tester, and the data of the standard requirements or control group are compared and analyzed.
[0051] Scanning Electron Microscope (SEM) analysis: observe the microstructural changes of modified soil samples through scanning electron microscope, and analyze the distribution and effect of modifiers in soil. The changes in gypsum surface morphology before and after modification, changes in soil strength and toughness characterizing materials, the connection mode between soil particles, the number of voids, the degree of pore development, and the generation of polymers are observed, and then the engineering properties before and after modification are studied and analyzed.
[0052] Combined with the 7D saturated compressive strength and SEM test results, the final target ratio of the modifier was determined to ensure the optimal performance of the modified soil sample in actual engineering.
[0053] By conducting joint determination of liquid and plastic limits, compaction tests, and shear strength tests on the samples, a certain improved mix ratio scheme can be screened out. Then, by conducting macro and micro tests on the above-mentioned dosages, the relatively optimal improved mix ratio can be further determined.
[0054] In summary, this method significantly improves the bearing capacity, water stability and shear strength of the soil through scientific screening and optimization of the modifier components. A series of scientific methods such as water dispersion test, orthogonal test, chemical and physical test, 7-day saturated compressive test, and microstructure analysis are used to gradually optimize the modifier ratio. The modification plan is customized according to the soil characteristics of the study area and specific engineering needs, which enhances the applicability of the modified soil. The durability and stability of the modified soil samples are improved, the frequency of later maintenance and renovation is reduced, and the long-term engineering costs are saved.
[0055] In some examples, the orthogonal experiments include a liquid-plastic limit combined determination test, a compaction test, and a shear strength test, and the expansion test includes a free expansion test, a no-load expansion rate test, and a loaded expansion rate test.
[0056] For example, the liquid limit and plastic limit combined determination test is a common test method for determining the liquid limit and plastic limit of soil. In this test, by determining the liquid limit, plastic limit, plasticity index and liquid index of the soil, the engineering properties of the soil, such as its bearing capacity, deformation characteristics and stability, can be understood. This information has important guiding significance for the engineering application of roadbed and provides a test basis for subsequent compaction tests.
[0057] Compaction test is a common test method used to evaluate the dynamic response and engineering performance of soil under impact load. This method uses a light compaction test, combined with material improvement technology, to study the relationship between the maximum dry density and the optimal moisture content of each improved material, further verify the accuracy, and obtain the maximum dry density of each dosage as a prerequisite for the subsequent dynamic triaxial compaction sample preparation.
[0058] The shear strength, cohesion c and internal friction angle φ of each improved soil sample were obtained through direct shear test. The instrument used in the experiment was strain-controlled direct shear apparatus.
[0059] Expansion tests include free expansion test, no-load expansion rate test and loaded expansion rate test.
[0060] The free expansion rate test is that the soil body expands and deforms due to the absorption of water molecules without its own structure. The ratio of the expanded volume to the original volume is the free expansion rate. The instruments used in the test are: a measuring cylinder with a range of 50mL, a measuring cup, and a NaCl solution with a concentration of 5%. Use a measuring cup to weigh 10mL of soil sample and pour it into the measuring cylinder. Then add 30mL of pure water and 5mL of a prepared 5% pure sodium chloride (NaCl) solution into the measuring cylinder. Stir the solution up and down with a glass rod, and finally rinse the glass rod and the wall of the measuring cylinder with pure water until the suspension reaches 50mL, and let it stand for 24 hours. After the solution surface is clarified, read the stable reading (the difference in the last 2 hours does not exceed 0.2mL); two measuring cylinders are used for parallel testing during the test, and the arithmetic mean is taken as the final result.
[0061] The no-load expansion rate is the expansion rate of the soil sample under the condition of no load but with lateral constraints. It can be used to simulate the expansion rate of the rock and soil mass in the absence of trains. Prepare the samples according to the optimal moisture content of each improved soil sample, bury the permeable stone with the same moisture content, fix the sample, and add the permeable stone and hole cover on the top. Install the micrometer and record the initial reading (set to 0.000mm after stabilization). Start to inject pure water into the container from top to bottom to 5mm from the top of the sample. Record the micrometer reading every 2 hours after water injection until the difference between the two readings of the micrometer does not exceed 0.01mm. The expansion is considered stable and the test is terminated.
[0062] Since the railway subgrade is affected by the dynamic load of the train and the stress of the overlying land, a loaded expansion rate test is considered when conducting the expansion test. The preparation and installation steps of the specimen refer to the unloaded expansion rate test. The difference is that after the micrometer is installed, a prestress of 1kPa is applied to make the instrument fully contact. Then record the initial reading of the micrometer, and apply the load in stages until the deformation is stable (the expansion per hour should not be greater than 0.01mm). Then add pure water from top to bottom to exceed the surface of the specimen by 5mm, and record the start time. After adding water, record the micrometer reading every 2 hours until the expansion is stable (the difference between the two expansions should not be greater than 0.01mm). The loaded expansion rate is calculated according to the following formula: is the expansion rate under load pressure P (%); is the reading after expansion stabilizes under load pressure P (mm); R is the instrument deformation under load pressure P ); is the micrometer reading before loading (mm); is the initial height of the specimen ; The expansion force test is to test the vertical stress generated by the test soil absorbing water molecules while keeping the volume of the soil sample unchanged. In the method, the expansion force generated by the sample is mainly due to the volume expansion caused by the anhydrite in the soil sample absorbing water molecules to form gypsum and the sulfate ions reacting with the substances in the cement to form other crystalline substances or flocculent substances.
[0063] In some examples, the orthogonal test is performed on the soil sample modified by the above-mentioned modifier to obtain the preliminary component information of the modifier, including: Determine the primary content of cement in the above-mentioned improver based on the above-mentioned liquid limit and plastic limit combined determination test; The primary content of polypropylene fiber and the primary content of sodium methyl silicate in the above-mentioned improver are determined based on the above-mentioned compaction test and the above-mentioned shear strength test.
[0064] For example, orthogonal experiment is an experimental design method used to study the effects of multiple factors and their interactions on the test results, so as to find the best ratio or combination in a smaller number of experiments. In this scheme, orthogonal experiment is used to determine the preliminary formula of the improver components to improve efficiency.
[0065] Soil is modified with conditioners to improve the physical and mechanical properties of the soil. Conditioners usually contain cement, polypropylene fiber and sodium methyl silicate. Each component plays a different role in soil modification, so experiments are needed to determine the optimal primary content of each component to achieve the optimal modification effect.
[0066] The liquid limit and plastic limit test is a key indicator for determining soil moisture content and is used to evaluate the plastic properties of soil. The liquid limit refers to the moisture content at which the soil changes from a plastic state to a liquid state, while the plastic limit refers to the moisture content at which the soil changes from a plastic state to a semi-solid state. The initial cement content in the modifier is determined based on the liquid-plastic limit combined determination test. Cement is a common soil stabilizer that can change the plastic and liquid properties of the soil, so its addition amount is preliminarily determined by the change in the liquid limit and plastic limit.
[0067] The compaction test is a test used to evaluate the density of soil and its optimal water content. The optimal dry density of the soil is obtained by compaction. This is very important for evaluating the engineering properties of soil. The shear strength test is used to measure the shear strength of the soil, which reflects the ability of the soil to resist shear failure. Shear strength has a direct impact on the stability and bearing capacity of the soil. The preliminary content of polypropylene fiber and sodium methyl silicate in the modifier is determined based on the compaction test and shear strength test. The role of polypropylene fiber is to increase the toughness and tensile strength of the soil, reduce the formation of cracks, and thus improve the overall stability of the soil. Sodium methyl silicate is a silicone waterproofing agent that can enhance the waterproof performance and durability of the soil.
[0068] Through these tests, the effects of the contents of these components on soil density and shear strength can be determined, and their dosage in the conditioner can be optimized. The preliminary content of each component in the soil conditioner (such as cement, polypropylene fiber and sodium methyl silicate) can be determined by combining various tests such as liquid limit, compaction and shear strength through orthogonal experimental design. This method can obtain an optimized conditioner formula with a smaller number of tests, thereby improving the engineering properties of the soil, such as plasticity, density and shear strength. Each component is preliminarily determined by different test methods to determine its optimal content in the conditioner to ensure that the ideal improvement effect is achieved in practical applications.
[0069] In some examples, the soil sample modified by the above-mentioned modifier is subjected to XRD test, expansion test and expansion force test to further narrow the preliminary component information of the above-mentioned modifier to obtain the narrowed component information, including: Based on the soil samples modified by the above-mentioned modifiers, XRD tests, swelling tests and swelling force tests are carried out to extract corresponding characteristic indicators and weight information corresponding to the characteristic indicators; Determine the mechanical property evaluation index based on all the above characteristic indicators and the weight information corresponding to the above characteristic indicators; Based on the above mechanical property evaluation index, the preliminary component information of the above improver is further limited to obtain the above limited component information.
[0070] For example, in soil modification, XRD can be used to analyze the new mineral phase formed after the amendment reacts with the soil to determine the effect of the amendment components on the mineral structure of the soil. By conducting XRD tests on soil modified with amendments, characteristic indicators related to the mineral composition of the soil after the amendment reaction can be extracted. This can help understand the chemical reactions of different amendment components in the soil and their effects.
[0071] The swelling test is used to determine the volume expansion characteristics of soil after absorbing water, and is particularly suitable for analyzing expansive soils. Expansive soils will significantly increase in volume after absorbing water, which has a great impact on the engineering properties of the soil and usually requires modification to reduce its swelling potential. The swelling test can be used to measure the inhibitory effect of the amendment on the soil swelling performance and extract characteristic indicators related to the improvement effect of the amendment on the soil swelling property.
[0072] The swelling force test is used to measure the swelling pressure generated by soil when it absorbs water and swells. The higher the swelling pressure, the greater the impact of the soil on the structure, so reducing the swelling force is one of the important goals of modification. The swelling force test is used to evaluate the inhibitory effect of the modifier on the soil swelling pressure. Through the test, the characteristic index of the modifier's inhibition of swelling force can be obtained.
[0073] By conducting XRD, swelling and swelling force tests on modified soil samples, multiple characteristic indicators related to the improvement effect can be extracted. These characteristic indicators may include but are not limited to: mineral component changes and crystal structure characteristics in XRD tests, soil volume changes (swelling rate) in swelling test, and swelling pressure values in swelling force test.
[0074] The determination of weight information refers to assigning a weight reflecting its importance to each characteristic indicator so that the importance of each characteristic indicator can be considered in the subsequent comprehensive evaluation.
[0075] Based on all characteristic indicators and their corresponding weight information, the mechanical performance evaluation index of the soil is determined by certain methods (such as multi-objective optimization, weighted summation, etc.). These evaluation indicators are used to reflect the comprehensive mechanical properties of the modified soil sample. Mechanical performance evaluation indicators can be used to comprehensively evaluate the improvement effect of the modifier on soil performance, such as shear strength, stability, expansion characteristics, etc.
[0076] After the components of the modifier are preliminarily determined, the characteristic indicators and evaluation indicators obtained from the above multiple tests can be used to further limit the preliminary components of the modifier, that is, to screen and adjust the content or type of the components to achieve better improvement effects. Limiting component information means that through the comprehensive evaluation of test results and mechanical properties, it is determined which modifier components have a more significant effect on performance improvement, thereby retaining the effective components, reducing the ineffective or side-effect components, and finally obtaining the optimized formula of the modifier. The characteristic indicators related to the improvement effect are extracted by performing XRD tests, swelling tests and swelling force tests on the modified soil samples, and then a comprehensive mechanical property evaluation system is constructed based on these indicators and their weight information. By comprehensively evaluating the modification effect of the soil, the components in the modifier are further screened and optimized to obtain a more accurate and effective ratio, thereby achieving optimal control of the soil modification effect. Such a process can not only improve the engineering performance of the soil, but also reduce unnecessary material waste and side effects.
[0077] In some examples, the mechanical performance evaluation index is determined based on all of the above characteristic indicators and the weight information corresponding to the above characteristic indicators, including: The performance evaluation index is calculated based on the following formula : in, is the number of all participating trials, For the The weight of the test results, For the The characteristic index value of each test, RD test characteristic indicators It is the mineral content ratio and characteristic index of free expansion test It is the free expansion rate and characteristic index of no-load expansion rate test It is the characteristic index of no-load expansion rate and loaded expansion rate test It is the load expansion rate and expansion force test characteristic index for expansion force; Based on the above mechanical property evaluation index, the preliminary component information of the above improver is further limited to obtain the above limited component information, including: A formula regression model is established based on historical test data, wherein the above formula regression model is based on the above mechanical properties evaluation , cement target content, polypropylene fiber target content and sodium methyl silicate target content; Determine the shrinkage limiting component information according to the mechanical property evaluation index and the formula regression model, wherein the shrinkage limiting component information includes a target cement content, a target polypropylene fiber content, and a target sodium methyl silicate content in the improver; The above formulation regression model is determined based on the following formula: in, is the target cement content, is the target content of polypropylene fiber, is the target content of sodium methyl silicate, and a, b, c, d, f, g and h are parameters obtained by regression fitting.
[0078] Exemplarily, based on the calculated MEI index, the preliminary improvement agent component information is further narrowed to obtain the information of the narrowed components, determine the final components and their optimal ratios, and thus improve the soil improvement effect. A linear regression model of each component of the improvement agent is established based on historical test data to quantify the impact of the improvement agent components on the MEI index. Using the regression equation, the final target content of each improvement agent component is determined based on the calculated MEI value. This can make the formulation of the improvement agent more scientific to ensure The method proposed in this embodiment uses the MEI mechanical property evaluation index to comprehensively evaluate the performance of the modified soil sample, and obtains an overall evaluation index by extracting the characteristic indicators of different tests and determining their weights. Then, multiple regression models are established to quantify the relationship between MEI and different modifier components, thereby determining the target content of each component and finally optimizing the modifier formula. This method can effectively improve the soil modification effect, reduce swelling, enhance mechanical properties, and achieve the optimal combination of modifier components.
[0079] In some examples, this also includes: Modifying the roadbed material based on the modifier corresponding to the content of the modifier component to obtain a modified roadbed material; A dynamic triaxial test is performed based on the modified roadbed material to obtain a first test result; Conducting a simulation test based on the modified roadbed material to obtain a second test result; The content of the above-mentioned improver component is optimized based on the above-mentioned first test results and the above-mentioned second test results.
[0080] For example, the dynamic triaxial test is a basic test method in soil mechanics. It applies dynamic loads to soil samples to simulate the complex stress state of the soil under actual working conditions, so as to study the mechanical behavior and deformation characteristics of the soil under dynamic loads. Including dynamic parameters such as the dynamic elastic modulus and dynamic Poisson's ratio of the soil, the fatigue performance, cumulative deformation characteristics of the soil and the failure mechanism of the soil structure can also be studied.
[0081] In the dynamic triaxial test, the roadbed material is subjected to axial cyclic loads, so that its bearing capacity, stiffness and fatigue resistance can be measured. The first test results are obtained through the dynamic triaxial test. These results include the mechanical performance of the material under dynamic loads, such as dynamic modulus, shear strength, accumulated strain and other parameters. These parameters can be used to determine the performance of the modified roadbed material in the actual road. Simulation testing is a way to simulate the behavior of modified materials under actual environmental conditions through computer technology. Simulation usually uses numerical methods such as finite element analysis (FEA) to simulate the stress of the modified roadbed material in the road structure by inputting material parameters, boundary conditions and load conditions.
[0082] The second test results are obtained through simulation, including displacement, stress distribution, deformation characteristics, etc. of the material under different stress states. These results can provide virtual test data for the real roadbed and help better understand the performance of materials under complex stress conditions.
[0083] Based on the first test results (dynamic triaxial test) and the second test results (simulation), the component content of the modifier is optimized. The first test results provide the physical response of the modified material under actual load, such as deformation and fatigue performance; the second test results provide virtual performance under various complex boundary conditions, including stress and strain distribution.
[0084] By comparing and analyzing the results of these two tests, we can find the influence of the modifier components on the material properties, and then determine which components need to be adjusted to achieve a better modification effect. Optimization methods may include adjusting the cement content, polypropylene fiber dosage, sodium methyl silicate ratio, etc. in the modifier to ensure that the performance of the modified roadbed material is optimal under both dynamic and static loads.
[0085] The optimized modified material should be able to withstand higher loads without significant deformation or damage. Under cyclic loading, the optimized material should show lower cumulative strain to reduce subgrade settlement and uneven deformation. The durability of the material under long-term traffic loads should be enhanced to extend the service life of the subgrade. By optimizing the components of the modifier, it is ensured that the subgrade material remains stable in a humid environment and does not lose strength due to water absorption.
[0086] In some examples, the above-mentioned simulation test is implemented based on a scale model established based on COMSOL software, and the above-mentioned scale model includes rails, CA mortar layer, track plate, roadbed and foundation structure. The above-mentioned scale model is a two-dimensional model. The load in the above-mentioned simulation test is a half-sine wave pulse. In the above-mentioned simulation test, infinite domain boundaries are used on the foundation and cross-section.
[0087] For example, Fig.17 As shown, this application uses COMSOL software to establish a 1:1 model with the railway roadbed, with an overall height of 8m, of which the height of the roadbed is 3m, and the slope on both sides of the subgrade is 1:1.5. The analysis model mainly includes rails, CA mortar layer, track slab, roadbed (consisting of subgrade surface layer, subgrade bottom layer, embankment body), foundation and other structures. The materials of the subgrade and the materials in the embankment are regarded as isotropic bodies, and only the load effect on the locomotive in the vertical direction is analyzed. The geometric model of the established mathematical model is simplified to a two-dimensional problem, which can reduce the amount of calculation without affecting the calculation accuracy, which is in line with practical significance. The finite element model finally established is as follows Fig.17 The figure shows the original model built according to the original size. Fig.18 This is a partial enlarged view of the model after meshing.
[0088] Solving the roadbed filling in the finite element method is a very complex problem. The model is relatively idealized and cannot be 100% consistent with the on-site working conditions. Therefore, we need to set the relevant parameters and some related assumptions: (1) The non-anisotropy of soil is ignored and the soil is regarded as an isotropic porous medium; (2) Since the density of the improved soil is good, the soil is regarded as an elastic body and the effects of other coupling fields are not considered; (3) The solid material is uniformly homogenized, and the overall change only occurs as the operator's parameters change.
[0089] According to the dynamic triaxial test, it was finally found that the performance of the samples of 4% cement + 0.25% polypropylene fiber + 2% sodium methyl silicate (XCF2) and 6% cement + 0.25% polypropylene fiber + 2% sodium methyl silicate (XCF3) in roadbed engineering met the relevant specifications and standards. Considering the economic benefits, the test data of 4% cement + 0.25% polypropylene fiber + 2% sodium methyl silicate was finally selected as the simulation parameters of fill.
[0090] In the numerical simulation, only the deformation degree of the improved soil under different burial depths and different frequencies is considered under the vertical load. According to previous experience, the interaction force generated by the wheel-rail load on the lower object can be used with a half-sine wave pulse: The simulation of each model is performed ten thousand times and can be controlled by time. The time of simulated load can be obtained from the load frequency. After previous analysis, the dynamic stress amplitude applied this time is 90MPa, and the load frequency is 1Hz, 2Hz, and 4Hz. It can be seen that the corresponding period T is 0.5s, 0.25s, and 0.125s, and the burial depth is 2.5m, 5m, and 7.5m. From the perspective of simulation, it is simplified to the surface layer of the roadbed, the bottom layer of the roadbed, and the main part below the roadbed.
[0091] Since the foundation is an infinite model, and this simulation test is to extract a part of it, infinite domain boundaries are used on the foundation and cross-section. In order to more clearly and intuitively express the surface deformation of each layer of the roadbed, the software is used to form an assembly by forming a union with each other, and then setting the contact pairs between each other to achieve the setting of conditions. For other domains, points and boundaries, fixed boundary conditions, roller supports and load boundaries are used to solve such problems.
[0092] Since the material in the modeling has a certain gravity, the gravity stress balance must be performed before the simulation. By calculating its initial gravity stress, each part is added as an external stress in the form of a tensor and transferred to each soil layer to balance the gravity of the simulated soil layer. High-speed railway and ballastless track subgrades have strict requirements on deformation. There are currently no clear regulations on the control of subgrade deformation during operation. Therefore, the improved control deformation is based on the uplift deformation control of the expansive soil subgrade. According to the relevant provisions of the "Railway Subgrade Design Code", refer to Article 9.2.1 of the "High-speed Railway Design Code" (TB10621-2014), the deformation is controlled to be no more than 2mm. For the sake of strictness, the subgrade bottom layer and the body below the subgrade are regarded as having a deformation limit value of 2mm, and the deformation displacement is observed using a probe diagram.
[0093] Fig.19A 2Hz numerical simulation diagram of each part before and after improvement provided for the embodiment of the present application, after the embankment is subjected to 10,000 cycles of load loading, the relationship between the vertical displacement deformation of the embankment and the frequency and the embankment part can be further seen from the above figure. From the overall point of view, the vertical displacement decreases with the increase of frequency and decreases with the increase of filling depth. This law is consistent with the law of dynamic triaxial test. From the point of view of the embankment part, the vertical deformation of the unimproved embankment surface layer is the largest, reaching more than 10mm under all load frequencies, and the maximum value reaches more than 20mm. The vertical deformation of the embankment body is the smallest, but most of the values are also above 10mm. From the load frequency, the vertical displacement on the y-axis shows a nonlinear decreasing trend with the increase of frequency. When the frequency is 1Hz, the vertical deformation is the largest, and when it is 4Hz, it is the smallest. Although the vertical deformation at 1Hz and 2Hz has a certain change and the amplitude between 2Hz and 4Hz is still relatively small, no matter which frequency has exceeded the 2mm specified in the specification. It can be analyzed from the improved filling roadbed that the overall law of its deformation influencing factors is consistent with the dynamic triaxial test. The difference is that after 10,000 cycles of loading, the vertical deformation of each improved part has been significantly improved. The largest vertical displacement is when the load frequency is 1Hz and the filling part is the roadbed surface layer, the deformation value is 1.92mm, which is 91.48% lower than the 22.54mm before improvement; the smallest vertical displacement is when the load frequency is 4Hz and the filling part is the roadbed body, the deformation value is 0.537mm, which is 88.14% lower than the 4.527mm before improvement. It can be seen that the deformation of the improved paste-containing silty mudstone roadbed can basically meet the engineering deformation requirements of railway roadbed filling materials.
[0094] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for modifying paste-containing sandy mudstone, characterized in that: include: Making an improver based on cement, polypropylene fibers and sodium methyl silicate; The modifying agent is used to mix and modify the paste-containing sandy mudstone to obtain modified rock and soil.
2. The method for modifying paste-containing sandy mudstone according to claim 1, characterized in that: The total mass of the improver is calculated as a percentage, and the improver comprises: 2% to 6% of the cement, 0.25% of the polypropylene fiber, and 0.25% to 0.5% of the sodium methyl silicate.
3. The method for modifying paste-containing sandy mudstone according to claim 1 or 2, characterized in that: The cement includes sulfate-resistant silicate cement, the length of the polypropylene fiber is 6 mm, the diameter of the polypropylene fiber is 23 um, the solid content of the sodium methyl silicate is 30%, the alkali content of the sodium methyl silicate is less than or equal to 12%, the silicone content of the sodium methyl silicate is greater than or equal to 18%, the specific gravity of the sodium methyl silicate is greater than or equal to 1.2 and less than or equal to 1.25, and the pH value of the sodium methyl silicate is greater than or equal to 12 and less than or equal to 13.
4. A method for determining the content of an improver component, used to determine the improver according to any one of claims 1 to 3, characterized in that: include: Determine the basic components of the improver based on a water dispersibility experiment, wherein the basic components include the cement, the polypropylene fiber and the sodium methyl silicate; Conducting orthogonal test on soil samples modified by the modifier to obtain preliminary component information of the modifier; Performing XRD test, swelling test and swelling force test on the soil sample modified by the modifier to further limit the preliminary component information of the modifier to obtain the limited component information; The target ratio of the improver is determined based on the 7D saturated compressive strength test and the microscopic electron microscope scanning test according to the shrinkage limiting component information.
5. The method for determining the content of the improver component according to claim 4, characterized in that: The orthogonal experiment includes a liquid-plastic limit combined determination test, a compaction test and a shear strength test, and the expansion test includes a free expansion test, a no-load expansion rate test and a loaded expansion rate test.
6. The method for determining the content of the improver component according to claim 5, characterized in that: The orthogonal test is performed on the soil sample modified by the modifier to obtain the preliminary component information of the modifier, including: Determine the primary content of cement in the improver based on the liquid-plastic limit combined determination test; The primary content of polypropylene fiber and the primary content of sodium methyl silicate in the improver are determined based on the compaction test and the shear strength test.
7. The method for determining the content of the improver component according to claim 5, characterized in that: The soil sample modified by the modifier is subjected to an XRD test, an expansion test and an expansion force test to further limit the preliminary component information of the modifier to obtain the limited component information, including: Based on the soil sample modified by the modifier, an XRD test, an expansion test and an expansion force test are performed to extract corresponding characteristic indicators and weight information corresponding to the characteristic indicators; Determine a mechanical property evaluation index based on all of the characteristic indicators and weight information corresponding to the characteristic indicators; The preliminary component information of the improver is further restricted based on the mechanical property evaluation index to obtain the restricted component information.
8. The method for determining the content of the improver component according to claim 7, characterized in that: The determining of the mechanical performance evaluation index based on all the characteristic indexes and the weight information corresponding to the characteristic indexes includes: The performance evaluation index is calculated based on the following formula : in, is the number of all participating trials, For the The weight of the test results, For the Characteristic index values of each test, XRD test characteristic index It is the mineral content ratio and characteristic index of free expansion test It is the free expansion rate and characteristic index of no-load expansion rate test It is the characteristic index of no-load expansion rate and loaded expansion rate test It is the load expansion rate and characteristic index of expansion force test for expansion force; Further limiting the preliminary component information of the improver based on the mechanical property evaluation index to obtain the limited component information, including: A formula regression model is established based on historical test data, wherein the formula regression model is based on the mechanical properties evaluation , cement target content, polypropylene fiber target content and sodium methyl silicate target content; Determine the shrinkage limiting component information according to the mechanical property evaluation index and the formula regression model, wherein the shrinkage limiting component information includes a target cement content, a target polypropylene fiber content, and a target sodium methyl silicate content in the improver; The formulation regression model is determined based on the following formula: in, is the target cement content, is the target content of polypropylene fiber, is the target content of sodium methyl silicate, and a, b, c, d, f, g and h are parameters obtained by regression fitting.
9. The method for determining the content of the improver component according to claim 4, characterized in that: Also includes: Modifying the roadbed material based on the modifier corresponding to the content of the modifier component to obtain a modified roadbed material; Performing a dynamic triaxial test based on the modified roadbed material to obtain a first test result; Conducting a simulation test based on the modified roadbed material to obtain a second test result; The content of the improver component is optimized based on the first test result and the second test result.
10. The method for determining the content of the improver component according to claim 9, characterized in that: The simulation test is implemented based on a scale model established with COMSOL software, the scale model includes rails, CA mortar layer, track plate, roadbed and foundation structure, the scale model is a two-dimensional model, the load in the simulation test is a half-sine wave pulse, and infinite domain boundaries are used on the foundation and cross section in the simulation test.
Citation Information
Patent Citations
Fiber reinforced concrete raw material, fiber reinforced concrete and preparation method and application thereof
CN110330273A
Fiber geopolymer improved soil and preparation method thereof
CN111620605A
Improved experimental method for sludge curing additive formula
CN118730803A
Composite concrete mechanical property prediction method, system, equipment and medium
CN118779969A
High-strength and high-toughness cement-based soil improving body using fiber reinforcement
JP2007270488A